2004
DOI: 10.2166/wst.2004.0603
|View full text |Cite
|
Sign up to set email alerts
|

Nitrite accumulation by aeration controlled in sequencing batch reactors treating domestic wastewater

Abstract: The feasibility of obtaining and keeping stable nitrite accumulation in Sequencing Batch Reactors (SBRs) treating domestic wastewater is studied. The final product of ammonium oxidation is either reproducible nitrate or nitrite depending on the aeration strategy. With the aerobic-anoxic sequence, two SBRs fed with domestic wastewater are operated in parallel. One SBR (SBR1) is controlled by the aeration control strategy, and the other SBR (SBR2) by alternate aeration control strategy. Based on the on-line indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
55
1
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(61 citation statements)
references
References 14 publications
2
55
1
3
Order By: Relevance
“…Therefore, low DO concentration is more restrictive for the growth of NOB than AOB, which will result in nitrite accumulation (Peng et al 2004a).…”
Section: Dissolved Oxygen Concentrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, low DO concentration is more restrictive for the growth of NOB than AOB, which will result in nitrite accumulation (Peng et al 2004a).…”
Section: Dissolved Oxygen Concentrationmentioning
confidence: 99%
“…According to Baumann et al (1997), an anoxic period of 4 h is sufficient to synthesize all enzymes and have complete denitrification. Besides, Peng et al (2004a) reported that using aeration control strategy partial nitrification had been achieved, although the temperature was decreased from 32 to 21°C.…”
Section: Operational and Aeration Patternmentioning
confidence: 99%
“…The accumulation of nitrite has also been shown to trigger the emission of nitrous oxide (N 2 O) during the denitrification step (Itokawa et al, 2001;Zeng et al, 2003a). Peng et al (2004) demonstrated that stable N removal via nitrite could be obtained through the control of the aeration time in a sequencing batch reactor (SBR) treating domestic wastewater. Aeration was stopped as soon as nitritation finished (i.e., complete oxidation of NH þ 4 ), as indicated by a bending point on the pH profile.…”
Section: Introductionmentioning
confidence: 99%
“…These potential benefits however come with challenges associated with NOB outselection under cold and diluted loading conditions. While the operational strategies are well documented for sidestream applications (Gut et al, 2005;Hellinga et al, 1998;van de Graaf et al, 1996;van Loosdrecht and Salem, 2005;Wett et al, 2007), many recent studies were conducted to address these challenges for mainstream applications using nitritation/denitritation (Blackburne et al, 2008;Gao et al, 2009Gao et al, , 2014Peng et al, 2004Peng et al, , 2012Regmi et al, 2013) and deammonification Hu et al, 2013;Lotti et al, 2013;Wett et al, 2013;Winkler et al, 2011) or both (Vlaeminck et al, 2012;. Several mechanisms were identified by which the three autotrophic groups, i.e.…”
Section: Introductionmentioning
confidence: 99%